Penerapan Model Pembelajaran Moving Class Terhadap Efektifitas Belajar Siswa - Riandi Riandi; Rizdki Elang Gumelar (Universitas Mathla'ul Anwar Banten, 2018)
This study aims to determine the effect of the application of moving class learning models on the effectiveness of student learning